Conflict Early Warning System Index as a Preventive Effort - Hadi Suyono (Journal of Educational, Health and Community Psychology, 2020)
The purpose of this study is to identify if a conflict is low, medium, or high level through  the development of the conflict early warning system index which  in turn serves  as a preventive  measure for conflict. The method used in this is the structural, sequential, and conjunctural model approach. Respondents of this study were farmers who were aware of issues regarding the Kulon Progo coastal land conflict and participated actively in the iron sand mining counter-movement. This study used proportional random sampling and obtained 279 subjects. Data collection used the Kulon Progo coastal area conflict scale, the categorization scale, the group identification scale, the group bias scale, the social resource scale, the motivational resource scale, the cognitive resource scale, the attitude scale, the subjective norm scale, and the perceived behavioural control scale. The research findings show that the conflict early warning system index is categorized as high and still latent. Based on this high index, it can be recommended that preventive measures should be taken by maintaining the land as an agricultural area so that the conflict does not manifest. This effort is beneficial for the farmers’ welfare, preserves the environment, and returns social capital. If implemented, this method can reduce the conflict index as it should be able to help peacefully maintain the social and cultural system of farmers.Keywords: index, early warning system, conflict, farmers.